A Nomogram Combing Peripheral Parameters for Estimation of CRSwNP Recurrence. Issue 5 (September 2021) - Du, Kun; Zheng, Ming; Zhao, Yan; Jiao, Chunyuan; Xu, Wenbin; Hao, Yun; Wang, Yue; Zhao, Jinming; Wang, Xiangdong; Zhang, Luo
Background: The preoperative prediction of the recurrence of chronic rhinosinusitis with nasal polyps (CRSwNP) remains difficult in clinical practice. Objective: We aimed to develop a nomogram that combined peripheral risk factors to clinically predict the recurrence of CRSwNP. Methods: Data from 158 CRSwNP patients who underwent endoscopic sinus surgery (ESS) from January 2012 to December 2016 were collected, and the patients were followed up for 3 years. Of these, 96 patients who underwent ESS in an earlier period formed the training cohort for nomogram development, and 62 patients who underwent ESS thereafter formed the validation cohort to confirm the model's performance. Risk factors for recurrence identified by univariate and multivariate logistic regression were used to create a nomogram. Results: The recurrence rate was 29.2% (28/96) for the training cohort and 35.5% (22/62) for the validation cohort. Univariate analysis identified blood eosinophils (Eos), serum IgE level, asthma comorbidity, and the number of previous ESSs as risk factors for recurrence. Among those four parameters, serum IgE level and a previous ESS surgery were identified as two independent risk factors. A nomogram consisting of blood Eos, total serum IgE level, asthma comorbidity, and the number of previous ESSs was constructed, demonstrating a C index of 0.81 (95% CI, 0.79-0.83) and 0.80 (95% CI, 0.77-0.83) for predicting recurrence in the training and validation cohorts, respectively. The nomogram had well-fitted calibration curves. Conclusion: The nomogram might be able to preoperatively predict the recurrence of CRSwNP by using currently available and objective parameters. Further studies are required to validate its reliability and effectiveness.